Pengaruh Debt To Equity Ratio Terhadap Return On Equity Pada Perusahaan Asuransi Syariah Di Indonesia - Dermawan, Surya (Journal Research of Economic and Bussiness, 2024)
This research aims to determine the influence of the Debt to Equity Ratio on Return on Equity in Sharia Insurance Companies in Indonesia. This research consists of the variable Debt to Equity Ratio (independent variable), and Return On Equity as the dependent variable. The data analyzed were the company's annual financial reports for the period 2019 to 2023. The research results showed that the test results showed that the Debt to Equity Ratio = 1.325 with a significant value for the Debt to Equity Ratio variable 0.000 < 0.05. So the research hypothesis can be accepted, namely that there is a significant influence between Debt to Equity Ratio on Return On Equity, partially.